Apoptosis as a mechanism of the albumin-induced kidney damage in childhood nephrotic syndrome - Burlaka, Ie.A.; Bagdasarova, I.V. (Ukrainian Journal of Nephrology and Dialysis, 2018)
It was shown previously on in vivo studies that proteinuria-induced effects play a crucial role in renal damage in chronic kidney disease (CKD). However, an initial mechanism of irreversible kidney damage in pediatric diseases characterized by chronic proteinuria, i.e. nephrotic syndrome, remains to be unclear. The aim of our work was to study the initial mechanism of kidney cells apoptosis development in nephrotic children. Methods.An examination of renal biopsies of 53 patients (aged 10 to 15 years) with nephrotic syndrome hospitalized in Pediatric Nephrology unit of the Children Clinical Hospital №7 (Kyiv, Ukraine) done. In vitro studies of albumin toxicity performed on rat proximal tubular cells in primary culture (RPTC). Results. Our study showed that albumin overload in nephrotic children leads to high levels of apoptosis. Its distribution and level varies regarding the level of focal segmental glomerulosclerosis (FSGS). The progression of sclerosis as a sign of irreversible kidney damage is accompanied by gradual increase in expression of proapoptotic factor Bax. In vitro studies on rat proximal tubular cells in primary culture (RPTC) showed that excessive albumin uptake into rat primary renal cells causes an almost immediate mitochondrial accumulation of the apoptotic factor Bax. We hypothesize that this might be initial pathway leading to kidney cells apoptosis in childhood nephrotic syndrome. Conclusions. We show thatoverexpression of apoptotic factor Bax has a place in children with nephrotic syndrome. Thus, chronic influence of albumin is a factor predisposing disturbances in system controlling apoptosis in this cohort of patients. Our data demonstrate that there is a dependence between the Bax overexpression level and the stage of CKD. We show the topologic difference between the Bax levels and FSGS degree. This is an indication thatdevelopment of glomerular and tubule-interstitial disorders under the influence of proteinuria occurs in specific range. In vitro data demonstrate that albumin overload causes mitochondrial Bax translocation that could be an initial factor in apoptotic pathway activation.